ROLE AND FUNCTION OF TRANSACTIONS IN DATABASE MANAGEMENT SYSTEMS - Jurayev Utkir Murodullo ugli (Scholars Digest Publishing, 2023)
In today's data-driven world, managing and maintaining vast amounts of information is crucial for organizations across industries. Database Management Systems (DBMS) play a pivotal role in ensuring the efficient handling of data. Within DBMS, transactions emerge as a cornerstone for data integrity, consistency, and concurrency. This article will explore the significance of transactions, their functions, and their impact on database management systems.
Keywords: Transactions in database management systems, Role of transactions in DBMS, Functions of transactions in databases, ACID properties in transactional systems.